Measurements of X-ray doses and spectra produced by picosecond laser-irradiated solid targets. (May 2017) - Yang, Bo; Qiu, Rui; Yu, Minghai; Jiao, Jinlong; Lu, Wei; Yan, Yonghong; Zhang, Bo; Zhang, Zhimeng; Zhou, Weimin; Li, Junli; Zhang, Hui
Abstract: Experiments have shown that high-intensity laser interaction with a solid target can generate significant X-ray doses. This study was conducted to determine the X-ray doses and spectra produced for picosecond laser-irradiated solid targets. The photon doses and X-ray spectra in the laser forward and side directions were measured using an XG III ps 300 TW laser system. For laser intensities of 7×10 18 –4×10 19 W/cm 2, the maximum photon dose was 16.8 mSv at 50 cm with a laser energy of 153 J on a 1-mm Ta target. The photon dose in the forward direction increased more significantly with increasing laser intensity than that in the side direction. For photon energies >300 keV, the X-ray spectrum can be fit with an effective temperature distribution of the exponential form, d N /d E = k × exp(− E / T x ). The X-ray temperature T x increased with the laser intensity in the forward direction with values of 0.46–0.75 MeV. T x was less strongly correlated with the laser intensity in the side direction with values of 0.29–0.32 MeV. The escaping electron spectrum was also measured. The measured electron temperature was correlated with the electron temperature predicted by the ponderomotive law. The observations in this experiment were also investigated numerically. A good agreement was observed between the experimental and simulation results. Highlights: We determined the X-ray doses and spectra for picosecond laser-irradiated solid targets. Photon doses and X-ray spectra in laser forward and side directions were measured. The photon dose in the forward direction increased more than that in the side direction. The measured electron temperature agreed with that predicted by the ponderomotive law.